Effects of indoor environment factors on productivity of university workplaces: A structural equation model. (1st April 2023) - Liu, Fengxuan; Chang-Richards, Alice; Wang, Kevin I-Kai; Dirks, Kim Natasha
Abstract: How are the indoor environment factors affecting the work productivity of office users in university buildings? Statistical analyses were undertaken on data probing building usage and self-reported indoor environment quality (IEQ) perception from a survey of 157 postgraduate students and 89 staff members at a university in New Zealand. Results of the partial least squares structural equational modelling confirmed the positive correlation among the IEQ within an office, the wellbeing and comfort as well as three dimensions of work productivity. IEQ factors relating to aesthetics and views were found to have the strongest effect on wellbeing and comfort as well as productivity for postgraduate students, whereas factors related to spatial and cleanliness are the most important for staff members. For both cohorts, the wellbeing and comfort in the office have significant direct effects on contextual performance, which indirectly further affects office users' ability in time management and task performance. The findings highlight the importance of the inclusion of design features that are productivity and wellbeing oriented across the building and the need for appropriate consultation with university office building users (e.g., students and staff) to achieve optimised design solutions. Highlights: A PLS-SEM was developed to illustrate the effects of indoor environment on productivity of university office users. IEQ factors have a direct effect on contextual performance and indirect effects on time management and task performance. Contextual performance has a significant direct effect on time management and task performance. Aesthetics and views have the largest effect on postgraduate, while spatial and cleanliness contribute the most for staff. It is important to consider to the effects of IEQ on productivity in tertiary building design.